Inmovilización de la güiña (leopardus guigna) en estado silvestre con la asociación anestésica ketamina-xilacina - Acosta, Gerardo; Funk, Stephan; Dunstone, Nigel (Avances en Ciencias Veterinarias, 2007)
The kodkod (Leopardus guigna) is one of the least known endangered felid species. In order to find an adequate anaesthetic association to handle safely kodkod individuals during ecological studies and veterinary procedures, we onducted 10 chemical immobilizations in 7 animals using a combination of ketamine hydrochloride (KH) and xylazine hydrochloride (XH) at the Laguna San Rafael National Park (Chile). A mean ( ±SE) dosage of 15.4 ±3.2 mg/kg KH and 1.7 ±0.3 mg/kg XH resulted in mean induction time of 4.6 ±2.9 min and a mean recovery time of 63.9 ±31.9 min. There was a direct relationship between KH dosage and the duration of the immobilization, with the combination of drugs leading to a shorter induction time. No secondary effects were observed. Based on our preliminary results, we recommended dosages of 11-12 mg/kg KH and 1.6-1.7 mg/kg XH.